2017
DOI: 10.1007/s10877-017-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Low near infrared spectroscopic somatic oxygen saturation at admission is associated with need for lifesaving interventions among unplanned admissions to the pediatric intensive care unit

Abstract: To investigate the association between low near infrared spectroscopy (NIRS) somatic oxygen saturation (<70%) at admission and the need for lifesaving interventions (LSI) in the initial 24 h of a PICU admission. Retrospective chart review of all unplanned admissions to the pediatric intensive care unit (PICU) with NIRS somatic oxygen saturation data available within 4 h of admission, excluding admissions with a cardiac diagnosis. LSI data were collected for the first 24 h after admission. Hemodynamic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 22 publications
1
28
0
1
Order By: Relevance
“…Decreased perfusion leads to increased oxygen extraction which results in lower rSO 2 measurements. In a retrospective study, Balakrishnan et al [18] evaluated low somatic NIRS values at pediatric intensive care admission in addition to other hemodynamic monitoring tools for critically ill children (serum lactate, severity of illness scores, heart rate, systolic blood pressure, arterial oxygen saturation, lactate level, acidosis) and need for life saving interventions (cardiopulmonary resuscitation, ECMO, invasive or noninvasive ventilation, emergent surgery, emergent dialysis, need for fluid resuscitation >40 mL/kg, blood product transfusion or vasoactive medications). They found a positive correlation between low somatic NIRS oxygen saturation and need for life saving interventions and a higher mortality rate in low NIRS group compared to normal NIRS group.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased perfusion leads to increased oxygen extraction which results in lower rSO 2 measurements. In a retrospective study, Balakrishnan et al [18] evaluated low somatic NIRS values at pediatric intensive care admission in addition to other hemodynamic monitoring tools for critically ill children (serum lactate, severity of illness scores, heart rate, systolic blood pressure, arterial oxygen saturation, lactate level, acidosis) and need for life saving interventions (cardiopulmonary resuscitation, ECMO, invasive or noninvasive ventilation, emergent surgery, emergent dialysis, need for fluid resuscitation >40 mL/kg, blood product transfusion or vasoactive medications). They found a positive correlation between low somatic NIRS oxygen saturation and need for life saving interventions and a higher mortality rate in low NIRS group compared to normal NIRS group.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that NIRS monitoring can aid in assessing perfusion and guiding interventions during transport ( 78 ). Some authors have suggested that low NIRS readings highlight the need for additional lifesaving interventions such as fluid resuscitation and/or vasopressors ( 40 , 41 , 79 ). Therefore, NIRS monitoring may enable early recognition of re-arrest, especially in PEA, and poor cerebral circulation during EMS resuscitation protocol.…”
Section: Use Of Nirs For Earlier Detection Of Re-arrest In Prehospitamentioning
confidence: 99%
“…This issue was assessed in this journal in February 2018 by Balakrishnan et al [14] in pediatric ICU patients with respect to the requirement for lifesaving interventions in the first 24 h following ICU admission. The use of such interventions, e.g.…”
Section: Nirs-derived Variables and Outcomementioning
confidence: 99%